THERAPEUTIC MUD OCCURRENCES IN GREECE: MINERALOGICAL AND GEOCHEMICAL COMPOSITION OF THE SAGIADA MUD (THESPROTIA PREFECTURE) - Athanassoulis, C.; Zaimis, S.; Chatziapostolou, A.; Agalaniotou, S. (Bulletin of the Geological Society of Greece, 2016)
The current study presents the preliminary results of the mineralogical and geochemical characterization of the Sagiada mud (Prefecture of Thesprotia), which is considered as one of the most representative therapeutic mud occurrences in Greece. This work is part of a bigger project, conducted by IGME (Athens, Greece), for the characterization of the Greek therapeutic mud deposits. The mineralogical composition was determined using X-Ray Diffraction (XRD), Differential Thermal Analysis (DTA), optical microscopy and Scanning Electron Microscopy (SEM). The main mineral phases of the Sagiada mud are quartz, feldspars, clay minerals such as illite, kaolinite, chlorite and vermiculite, and calcite accompanied by minor phases such as halite and pyrite. Traces of muscovite and gypsum were also identified. Geochemical analyses were performed using X-Ray Fluorescence (XRF) and Inductively Coupled Plasma-Mass Spectrometry (ICP-MS) for the determination of major and trace element content, respectively. Compared to Spanish peloids and European floodplain sediments, the Sagiada mud reveals an analogue chemical composition.